2010
DOI: 10.1080/00224499.2010.521899
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gaze Behavior towards Sexually Preferred and Non-Preferred Human Figures

Abstract: The gaze pattern associated with image exploration is a sensitive index of our attention, motivation and preference. To examine whether an individual's gaze behavior can reflect his/her sexual interest, we compared gaze patterns of young heterosexual men and women (M = 19.94 years, SD = 1.05) while viewing photos of plain-clothed male and female figures aged from birth to sixty years old. Our analysis revealed a clear gender difference in viewing sexually preferred figure images. Men displayed a distinctive ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 31 publications
7
66
1
Order By: Relevance
“…Fixation locations were then extracted from the raw eye-tracking data using velocity (less than 0.2° eye displacement at a velocity of less than 20°/s) and duration (greater than 50 ms) criteria (Guo, Mahmoodi, Robertson, & Young, 2006). To determine gaze allocation within key body regions (Hall, Hogue, & Guo, 2011), each body was divided into five regions of interest: face (including hair), upper-body (from the base of the neck to the end of the rib cage), waist-hip region (including the stomach, hips, and pubic region), arms (including hands) and legs (including feet). The viewing time allocated to each region was normalised in proportion to the total viewing time sampled in that trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixation locations were then extracted from the raw eye-tracking data using velocity (less than 0.2° eye displacement at a velocity of less than 20°/s) and duration (greater than 50 ms) criteria (Guo, Mahmoodi, Robertson, & Young, 2006). To determine gaze allocation within key body regions (Hall, Hogue, & Guo, 2011), each body was divided into five regions of interest: face (including hair), upper-body (from the base of the neck to the end of the rib cage), waist-hip region (including the stomach, hips, and pubic region), arms (including hands) and legs (including feet). The viewing time allocated to each region was normalised in proportion to the total viewing time sampled in that trial.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent eye-tracking studies have observed that in the tasks of free-viewing, body attractiveness and body fat judgement, both male and female viewers demonstrated similar gaze distribution with more gaze allocated at the waist-hip and chest areas (Cornelissen, Hancock, Kiviniemi, George, & Tovée, 2009;Hall, Hogue, & Guo, 2011). These observations of both genders using the same visual features to assess female body could be accounted for by mate selection theory, which postulates women judge their own attractiveness relative to other women in order to assess their own likelihood for successful mate selection (Buss, 2003) or monitor potential competitors as attractive women have high 'market value' (Hughes, Harrison, & Gallup, 2004;Pawlowski & Dunbar, 1999) and pose a greater threat to partner sexual fidelity (O'Connor & Feinberg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that women gaze upon other women, similar to men but potentially for differing reasons such as body comparison (Hall et al, 2011).…”
Section: Masquerading Gender At the Festival Sitementioning
confidence: 99%
“…This contrast may be enhanced further by movement of the nuchal crest and of coloured objects in the male's beak. In addition to affecting female perception of colour, chromatic adaptation can also affect the ability to discriminate among colours [31], and interact strongly with eye movements [32,34], which may affect mate assessment and attractiveness [35]. These potential knock-on effects highlight the many unexplored avenues in the interaction between visual mechanisms and sexual displays [36].…”
Section: Discussionmentioning
confidence: 99%